Resilience of Phialocephala fortinii s.l. – Acephala applanata communities – Effects of disturbance and strain introduction. (February 2018) - Stroheker, Sophie; Dubach, Vivanne; Queloz, Valentin; Sieber, Thomas N.
Abstract: Members of the Phialocephala fortinii s.l. – Acephala applanata species complex (PAC) are ubiquitous endophytes forming complex communities in roots of conifers and ericaceous shrubs across the Northern hemisphere. Two kinds of disturbances (clear-cutting and drought) and their effects on the resident PAC community, as well as on the introduction of alien strain 7_45_5, were investigated using mesocosms with natural Norway spruce ( Picea abies ) regeneration, both under controlled climate chamber conditions and natural conditions in the forest. This is the first record of successful strain introduction into a well-established forest ecosystem. Introduction was more successful when planting inoculated living spruce saplings, compared to inoculation using autoclaved colonized roots. 7_45_5 was less assertive in the forest, where Phialocephala subalpina clearly dominated. Clear-cutting favored A. applanata and simultaneously reduced the overall frequency of PAC. Drought only had a significant influence on 7_45_5, which was more abundant in dry than moist, non-clear-cut plots. To conclude, disturbances and arrival of foreign strains can alter resident PAC communities significantly.